THE MODERN METHODS OF ANALYSIS OF OXIDIZED AND REDUCED FORMS OF COENZYME Q₁₀ IN BIOMATERIAL (REVIEW) - V. I. Zozina; O. A. Goroshko; L. M. Krasnykh; V. G. Kukes (Разработка и регистрация лекарственных средств)
In the human body, coenzyme Q10 is in the oxidized and reduced forms and can be found in every organ. The review describes modern HPLC methods of coenzyme Q10 analysis using electrochemical, spectrophotometric and mass spectrometric detectors. In the article we present information on sampling, preparation of biomaterial for analysis and preservation of coenzyme Q10 stability in biomaterial. It is carried out a comparative analysis of the determination methodologies for the oxidized and reduced forms of coenzyme Q10 by its sensitivity and selectivity.